Terrestrial isopods of the genus Porcellio Latreille, 1804 (Isopoda; Oniscidea) in Iran, with a description of a new species - Kashani, Ghasem M.; Ahdiyeh, Abedini; Zahra, Hatami (Zootaxa, 2017)
Terrestrial isopods of the genus Porcellio Latreille, 1804 were investigated in Iran. Porcellio obsoletus Budde-Lund, 1885 was found only in northern Iran while P. evansi Omer-Cooper, 1923 is broadly distributed in the country. Porcellio rubidus Budde-Lund, 1885 was deemed as a senior synonym of P. evansi. Porcellio mehrdadi sp. nov. was described and its diagnostic characters were figured. The new species is characterized by the male pereopod VII ischium with a setose field on sternal margin and a setose area on rostral surface.